Study of aeromagnetic data over part of eastern ghat mobile belt and Bastar craton - Anand, S. P.; Rajaram, M. (My University, 2003)
A portion of the aeromagnetic anomaly map of India, from 170 to 200 N and 78o to 84o E has been analysed to understand the tectonics of the region. The distribution of magnetic sources in the study region are clearly brought out in the analytic signal map and found to be associated with charnockitic rocks, iron formation and trap flows. The Godavari Graben is devoid of any magnetic sources. High-grade charnockitic rocks on surface and sub-surface, flank the shoulders of the Godavari Graben on either side. From the analysis of magnetic data, Sileru Shear Zone (SSZ) is identified as the contact of the Bastar craton and the Eastern Ghat Mobile Belt (EGMB). The Eastern Ghat is divided into two blocks: Block-N north of Srikakulam is devoid of magnetic sources while the charnockitic rocks are the main magnetic carriers in Block-S. The difference in magnetic characteristics of the two blocks has been attributed to the difference in metamorphic history. Block-N has an over print of amphibolite facies metamorphism while Block-S to the south depicts granulite facies metamorphism. The Euler solutions within the EGMB shows that the magnetic sources along SSZ is shallower than the south east implying that the exhumation process in the EGMB has a differential rate.
Keywords: Aeromagnetic anomaly; Dharwar; Bastar; Eastern Ghats; Metamorphism; Aeromagnetic data; EGMB